Analisis Potensi Sonneratia sp. di Wilayah Pesisir Pantai Timur Surabaya Melalui Pendekatan Ekologi dan Sosial-Ekonomi [Potency Analysis Of Sonneratia sp. At East Coast Surabaya Through Ecology and Social Economy Studies] - Kustiawan Tri Pursetyo; Wahju Tjahjaningsih; Sapto Andriyono (Faculty of Fisheries and Marine Universitas Airlangga, 2013)
Abstract The damages in mangrove forest recently rise due to the exploitation, either in farming or housing. It can cause the loss of mangrove function as marine ecosystem, affect marine biota survival, environment damage and reduce fishermen income in the future. For solving these problems, some efforts can be done by maximize the mangrove forest potential. Mangrove economic value analysis was done through two approaches. The first was Direct Use Value which use for knowing the benefit of the mangrove directly. The second was statistic analysis by multiple linear regression. The result of the research shows as many as 20 % of respondent make use of Sonneratia directly, either fruits, leaves or woods. Others, as many as 80% of respondents felt the benefit of Sonneratia indirectly. The research was done at mangrove forest of the Surabaya East Coast, East Java, Indonesia.